Adulterated slimming pills: an examination of the regulatory provisions and civil remedies for victims / Natrah Fareha Rahmat, Nurhanisah S H Sahul Hamid and Siti Syarah Mohd Sudin - Rahmat, Natrah Fareha; S H Sahul Hamid, Nurhanisah; Mohd Sudin, Siti Syarah (2008)
This research is conducted on our effort to investigate the law and regulatory body relating to pharmaceutical products, specifically on adulteration of slimming pills in Malaysia. The topic was chosen because we think that the enforcement of law existing now is still insufficient to control the scenario of adulterated slimming pills by irresponsible manufacturers. This is because since there are many previous cases where consumers have suffered injuries due to the consumption of dangerous slimming pills which have been adulterated. Therefore, the insufficiency of the law must be taken into account whether it can be enforced by having more appropriate alternatives. We believe that the government possesses the kinds of power in order to take actions to cope with the problems. Due to this, we also deem it proper and wise, in understanding this study, to present our findings from the research that we have conducted on this issue, whether this result could be an alternative to help the government to cope with adulteration matters. From the analysis made on the findings, we have suggested some recommendations.